A Rare Case of Multiple Cavernous Hemangiomas - O.K. Radhakrishnan; Khushboo Goyal; Varsha Manade; Shreya Gandhi (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
A 44-year-old gentleman came to the ophthalmology outpatient department with the chief complaint of protrusion of the left eyeball since 2 years associated with a progressive decrease in visual acuity and restriction of extraocular movements in the lateral gaze of the left eye. On examination, axial proptosis was noted in the left eye (LE) which was measured using Hertel’s exophthalmometer. The anterior segment examination and fundus examination showed no significant changes. A computed tomography (CT) scan and magnetic resonance imaging (MRI) were performed for the patient which revealed multiple lesions in the intraconal compartment. The patient underwent anterior orbitotomy through an inferior transconjunctival approach with lateral canthotomy and lateral cantholysis and the mass excised was sent for histopathological examination on which features were suggestive of cavernous hemangioma. Such a case of multiple cavernous hemangiomas is rarely seen.